Covid 19 in metropolitan Lima and Callao: poorest districts, the most affected? - Risco Franco, Carlos (2023)
The objective is to compare the mortality rates due to covid-19, between the poorest districts with the least poor districts, following the idea that the first ones would have the highest rates. To carry out this research, the poorest districts and the less poor districts were considered, for Metropolitan Lima and Callao, which were classified by the National Institute of Statistics and Informatics of Peru in 2018. Secondary information from the databases of the Ministry of Health and the National System of Deaths was used. The comparisons were made through the mortality rate due to covid-19, from March 2020 to December 2021. It was found that the mortality rate, due to covid-19, in most of the poorest districts was lower than that of less poor districts. It also turned out that, among the 7 districts of Metropolitan Lima with the highest mortality rates, no poorer district was found. In addition, a positive and significant correlation was found between the percentage of the population over 60 years of age in the districts of Metropolitan Lima and Callao and their respective mortality rates. Conclusion. In Metropolitan Lima and El Callao, the poorest districts, were not the most affected by covid-19, considering the mortality rate.